PENGUATAN LITERASI KEUANGAN DIGITAL MELALUI FINTECH DAN PENGEMBANGAN KEWIRAUSAHAAN BERBASIS MARKETPLACE UNTUK PEMBERDAYAAN KADER IMM KOTA MATARAM - Jafar, M. Ulfatul Akbar; Pratama, Inka Nusamuda; Nazwin, Asfarony Hendra; Subandi, Azwar (Nusantara Hasana Journal, 2025)
Digital transformation has driven significant changes in the financial and entrepreneurial sectors, making digital financial literacy and the effective utilization of technology fundamental needs for the younger generation. This community service activity aims to strengthen digital financial literacy through the use of financial technology (fintech) and develop marketplace-based entrepreneurship as an effort to empower members of the Mataram City Muhammadiyah Student Association (IMM). The activity employed a participatory action research approach, which was implemented through the stages of needs analysis, training, mentoring, business implementation, and monitoring and evaluation. The activity involved 120 IMM members with interests in and startups related to the creative economy. The results of the activity showed an increase in participants’ digital financial literacy scores of more than 30 percent, an increase in the use of digital financial recording applications in their businesses, and a rise in the number of active online stores on national marketplaces. Furthermore, the establishment of the Mataram City IMM collective marketplace is a strategic outcome that supports the institutional sustainability of the members’ businesses. This activity demonstrates that integrating digital financial literacy, fintech adoption, and marketplace-based entrepreneurship is effective in increasing the economic capacity of members and building sustainable economic independence. This community service program is expected to become a practical and replicable empowerment model for student organizations and other youth communities in navigating the dynamics of the digital economy